Geometrical reasoning in the determination of the order of factorial - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2008)
It is shown here how to interpret Stirling’s formula geometrically, moreover, how geometrical reasoningcan serve determining the proper magnitude of the logarithm of the factorial.
Keywords: factorial; geometrical interpretation; Stirling’s formula